(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2024)
Introduction: QoL is an assessment of how the individual health is affected over time by a disease, disability or disorder. COVID-19 is a disease caused by a new strain of coronavirus started from 2019 at Wuhan, China and spread all over the world including Nepal on 23 January after which lockdown was announced by Government of Nepal. Every disease has their unique way to affect QoL. The objectives of this study were to assess the quality of life among patient with and without COVID-19 and find the association of QoL score along with patient demographic variables. Materials and Methods: A quantitative retrospective cohort study was adopted and total 200 participants were selected through purposive sampling technique where 100/100 were patient without COVID-19 and with COVID-19. All the patients were selected from the hospitals of Madhesh Province. The data were gathered by using SF-36 Scale and then data were analyzed and interpreted. Results: The result revealed that in patient without COVID-19 more than one third 84% of patients were having moderate level of QoL and only 3% were having good level of QoL. Where as in patient with COVID-19 only 8% were having good level of QoL. Among the patient without covid-19, only age was significantly associated and in the patient with covid-19 presence of medical condition was associated. Conclusions: The effect of acute disease, chronic disease or any infectious disease has impact on Quality of Life. Thus, all medical facilities need to be aware of it and start using methods that can improve each patient’s quality of life.